2016
DOI: 10.1016/j.iccn.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of caring for the suddenly bereaved in adult acute and critical care settings, and the provision of person-centred care: A qualitative study

Abstract: Aim: To explore nursing interventions for person-centred bereavement care in adult acute and critical care settings.Design: A descriptive exploratory study, involving focused, face-to-face interviews.Participants comprised nine registered nurses and one auxiliary nurse, working in environments where sudden death was known to occur, i.e. emergency, cardiac and critical care. Interviews were transcribed verbatim and data subjected to directed content analysis. The provision of person-centred care was examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Nurses working in advocacy roles facilitated communication between families and medical teams, to assist in the understanding of end‐of‐life and bereavement care (Caswell et al . , Walker & Deacon ). Nurses were also identified as interpreters of information, being able to speak in ‘plain language’ for families and translating medical information to assist in decision‐making (Caswell et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses working in advocacy roles facilitated communication between families and medical teams, to assist in the understanding of end‐of‐life and bereavement care (Caswell et al . , Walker & Deacon ). Nurses were also identified as interpreters of information, being able to speak in ‘plain language’ for families and translating medical information to assist in decision‐making (Caswell et al .…”
Section: Discussionmentioning
confidence: 99%
“…, Slayter et al . , Walker & Deacon ). The systematic review similarly identified multidisciplinary collaboration, which was integral for the provision of bereavement care in acute hospitals (Pincombe et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate this engagement with patients and their families, researchers in a variety of programmes of care, dementia (Røsvik, Brooker, Mjorud, & Kirkevold, ); mental health (Beckett et al, ); and bereavement (Walker & Deacon, ), have used components of the PcPF. The lens of PcP has also been used to explore how the delivery of care is documented (Broderick & Coffey, ); to explore quality improvement methodologies (Bateman, Anderson, Bird, & Hungerford, ); and to inform reflection and practice development processes (Manley, O 'Keefe, Jackson, Pearce, & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional support and a meeting to review the events prior to patient death were the types of support most desired by bereaved family members who participated in this study. Researchers have also uncovered the emotional impact of nurses' exposure to dying, death and bereavement in ICU (Bloomer et al, 2015;Lima et al, 2018;Shorter and Stayt, 2010), and nurses' need for peer support, and reflective debriefing to give closure to events (Walker and Deacon, 2016).…”
mentioning
confidence: 99%